The p53 Family: A Role in Lipid and Iron Metabolism - Laubach, Kyra; Zhang, Jin; Chen, Xinbin (Frontiers in Cell and Developmental Biology, 2021)
The p53 family of tumor suppressors, which includes p53, p63, and p73, has a critical role in many biological processes, such as cell cycle arrest, apoptosis, and differentiation. In addition to tumor suppression, the p53 family proteins also participate in development, multiciliogenesis, and fertility, indicating these proteins have diverse roles. In this review, we strive to cover the relevant studies that demonstrate the roles of p53, p63, and p73 in lipid and iron metabolism.